Implementing the WHO Safe Childbirth Checklist: lessons from a global collaboration. Issue 3 (19th August 2017) - Perry, WRG; Bagheri Nejad, S; Tuomisto, K; Kara, N; Roos, N; Dilip, TR; Hirschhorn, LR; Larizgoitia, I; Semrau, K; Mathai, M; Dhingra-Kumar, N
Abstract : The WHO Safe Childbirth Checklist (SCC) was developed to ensure the delivery of essential maternal and perinatal care practices around the time of childbirth. A research collaboration was subsequently established to explore factors that influence use of the Checklist in a range of settings around the world. This analysis article presents an overview of the WHO SCC Collaboration and the lessons garnered from implementing the Checklist across a diverse range of settings. Project leads from each collaboration site were asked to distribute two surveys. The first was given to end users, and the second to implementation teams to describe their respective experiences using the Checklist. A total of 134 end users and 38 implementation teams responded to the surveys, from 19 countries across all levels of income. End users were willing to adopt the SCC and found it easy to use. Training and the provision of supervision while using the Checklist, alongside leadership engagement and local ownership, were important factors which helped facilitate initial implementation and successful uptake of the Checklist. Teams identified several challenges, but more importantly successfully implemented the WHO SCC. A critical step in all settings was the adaptation of the Checklist to reflect local context and national protocols and standards. These findings were invaluable in developing the final version of the WHO SCC and its associated implementation guide. Our experience will provide useful insights for any institution wishing to implement the Checklist.